Pemanfaatan Nanopartikel Berbasis Tumbuhan sebagai Agen Antibakteri Ramah Lingkungan - Desi Reski Fajar; Dedy Ma'ruf (Journal of New Trends in Sciences, 2024)
Antibiotic resistance has emerged as a significant global health challenge, prompting the exploration of alternative antimicrobial agents. This study focuses on the synthesis and antibacterial potential of plant-based nanoparticles, specifically silver nanoparticles AgNPs, synthesized using neem leaf extract Azadirachta indica. The research aims to assess the effectiveness of these green-synthesized nanoparticles against Escherichia coli E. coli), a common pathogen responsible for numerous infections, including those resistant to conventional antibiotics. The synthesis of AgNPs was performed using neem leaf extract as a reducing and stabilizing agent, following a green synthesis approach that is environmentally friendly and avoids harmful chemicals. The synthesized nanoparticles were characterized using UV-Vis spectroscopy, Transmission Electron Microscopy TEM, and X-ray Diffraction XRD, ensuring the particles’ size, shape, and crystalline structure were in the desired range. Antibacterial activity was assessed using the agar diffusion method, comparing the inhibition zones formed by the nanoparticles with those of traditional antibiotics. The findings revealed that the silver nanoparticles displayed significant antibacterial activity against E. coli, with inhibition zones comparable to conventional antibiotics, indicating their potential as an effective alternative in combating antibiotic-resistant bacteria. Moreover, these nanoparticles exhibited high stability and biocompatibility, making them a promising candidate for further biomedical applications. The results suggest that neem-based AgNPs could serve as an eco-friendly solution for addressing antibiotic resistance. Future research is recommended to explore the broad-spectrum activity of these nanoparticles against other bacterial pathogens and to assess their safety and efficacy in clinical settings.